La función del estado de naturaleza en el Origen de la desigualdad entre los hombres - Prieto, Martín (2011)
This work is aimed at developing and analyzing the theoretical concept of\nthe state of nature, as described by Jean Jaques Rousseau in On the origin of inequality,\ndetermining the intention underlying such concept, its role in the essay?s argument and\nits relation with the author?s general objective, more thoroughly developed in The social\ncontract. Further, I will explain the reasons why I consider that historical, anthropological and psychological interpretations are unfeasible, playing down the importance\nof human nature?s description still included in the text. Finally, I will come up with\nthe conclusion that this theoretical concept, grounded on philosophical considerations,\nis intended to be the basis of a political model that, from a prescriptive view, will shape\nethical and political ambitions.\nParticularly, I will provide arguments against John Scott?s position, who supports a psychologist\ninterpretation of the Second Discourse but, at the same time, I will suggest\nthat its speculative value was not impaired by its prescriptive nature. Finally, I will use\nAristotle?s theory on poetry and Ricoeur?s considerations on writing, in order to defend\nthe state of nature?s capacity to reflect mankind?s political possibilities, based on the\njusnaturalist view of history and political philosophy\n